1993
DOI: 10.1159/000196235
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Emphysema followed by Pulmonary Fibrosis of Undetermined Cause

Abstract: Idiopathic pulmonary fibrosis (IPF) and pulmonary emphysema (PE) have distinct clinical and pathological characteristics, and have been considered to be separate disorders. However, recent animal experiments have suggested that, with regard to their pathogenesis, the diseases have some features in common. However, there are no clinical data supporting this hypothesis. We report here 9 patients (all male, 67 ± 2 years, mean ± SE) who had PE followed by IPF. They were found among 152 PE patients who came to Toho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 6 publications
4
29
0
5
Order By: Relevance
“…In 1993 Hiwatari et al described nine patients with pulmonary emphysema followed by IPF and all of these patients were male and heavy smokers. 1 In 2004 Odani et al reported 31 patients diagnosed with coexisting pulmonary emphysema and idiopathic pulmonary fibrosis among 14900 patients examined by chest CT. 2 The CT of all patients showed the coexistence of emphysema with an upper lung field predominance and diffuse parenchymal lung disease with significant pulmonary fibrosis predominantly in the lower lung fields . The incidence of lung cancer was 42% (13 patients) and squamous cell carcinoma was the most common histological type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993 Hiwatari et al described nine patients with pulmonary emphysema followed by IPF and all of these patients were male and heavy smokers. 1 In 2004 Odani et al reported 31 patients diagnosed with coexisting pulmonary emphysema and idiopathic pulmonary fibrosis among 14900 patients examined by chest CT. 2 The CT of all patients showed the coexistence of emphysema with an upper lung field predominance and diffuse parenchymal lung disease with significant pulmonary fibrosis predominantly in the lower lung fields . The incidence of lung cancer was 42% (13 patients) and squamous cell carcinoma was the most common histological type.…”
Section: Discussionmentioning
confidence: 99%
“…Those patients were all males and heavy smokers. 1 Odani et al reported 31 patients with pulmonary emphysema and IPF among 14,900 patients who underwent chest CT and 13 of the 31 (42%) also had lung cancer. 2 Cottin et al conducted a retrospective study of 61 patients with combined pulmonary fibrosis and emphysema (CPFE) and comprehensively described the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, although smoking seems to be a risk factor for IPF (3), it appears to confer some protection for survival, putatively because it reduces fibroblastic foci (20,21). Furthermore, heavy smokers may develop first pulmonary emphysema and then pulmonary fibrosis of unknown etiology (14).…”
Section: Discussionmentioning
confidence: 99%
“…Having traditionally been considered as separate disorders, recent studies suggest that the diseases are more commonly associated than previously considered [1]. Indeed, several groups have described series of combined pulmonary fibrosis and emphysema (CPFE) [1][2][3][4], with upper lobe emphysema and pulmonary fibrosis of the lower lungs [5]. Initially reported to be coincidental and not comprehensively described [6], CPFE has been proposed as a distinct syndrome [3,7,8].…”
mentioning
confidence: 99%